CO2 Laser Treatment of Xanthelasma Palpebrarum in skin, Aden, Yemen - Amer Bin Al-Zou; Asia Hassan Abdulla Saleh; Khaled Husein Algaradi; Fathi Elkasah (Sirte Journal of Medical Sciences, 2022)
Background: Xanthelasma palpebrarum clinically presents as yellowish plaques on the upper and/or lower eyelids. CO2 laser is considered the gold-standard for its treatment. Objectives: To evaluate the effectiveness of CO2 laser in the treatment of patients with xanthelasma palpebrarum. Patients and methods: Fifty eight patients were presented to our clinics in Almansoora and Khormakser in Aden, during the period January 2020 to December 2020 with xanthelasma palpebrarum and treated with CO2 Laser. Results: The study patients were 58 included in the study, the females were (81%) and the males were (19%). The mean age of all patients was 49.2 ± 9.4 years and their age ranged between 32 – 68 years (p ≤0.05). The age group 50 years old and less represent (53.4%). We treated the patients with CO2 laser and the results were excellent among (75.9%) patients and good results among (17.2%) patients. More excellent results were among patients aged ≤ 50 years old, good results were predominant among patients aged more than 50 years old. The difference between values was statistically significant (p = 0.005). We observed the side effect as follows: hypopigmentation in (10.3%) patients, hyperpigmentation in (3.4%) patients and erythema in (5.2%). Three patients (5.2%) developed a recurrence of xanthelasma. In our study cholesterol level was found high in (17.2%) distributed among patients of age group ≤ 50 years old with (5.2%) and among age group > 50 years old with (12.1%) patients. Conclusion: In our study, excellent results were predominant followed by few numbers of good results. Further studies needed for more patients.